Perceived Usefulness, Self-Efficacy, and Emotional Engagement: Does It Affect Student’s Satisfaction while using the Platform? - Iffa Masruroh; Jun Surjanti; Ni’matush Sholikhah (AL-ISHLAH: Jurnal Pendidikan, 2021)
Many students are dissatisfied with using blended learning platforms. At the same time, student satisfaction with a blended learning platform can determine the quality of learning and learning outcomes. This study analyzed the direct and indirect influence between the user perception of a blended learning platform, self-efficacy, and emotional engagement on student satisfaction. This research includes quantitative research with a type of causality—grade XI students of IPS SMA 14 Negeri Surabaya as a population. A sample of 103 students was taken using saturated sample techniques. Data collection is obtained through interviews, questionnaires, and documentation. The data analysis used is path analysis. The results directly influenced perceptions of the usefulness of blended learning platforms, self-efficacy, and emotional engagement on student satisfaction. The indirect influence between the perception of usefulness of platform and self-efficacy to student satisfaction through emotional engagement.